THE POLITICS OF TIME AND STATE IDENTITY IN THE GERMAN DEMOCRATIC REPUBLIC. (December 2019) - Colla, Marcus
ABSTRACT: The communist regimes of Eastern Europe carried a particular set of assumptions about the way past, present and future related to one another. In the case of the German Democratic Republic (the GDR), these assumptions manifested themselves in official language and propaganda as a defence of the regime's dynamic and forward-looking historicity against the 'ahistorical' and 'nostalgic' modes of understanding that supposedly typified the historical consciousness of its West German adversary. By this view, the German Federal Republic – and the capitalist West more generally – lacked both a meaningful past and a meaningful future. This article investigates how the East German regime articulated its historicity as a direct expression of its state identity. In particular, it examines how it sought to rationalise newly emerging historical and cultural practices in the GDR within the framework of a modern and progressive socialist historicity, and how it deployed these as an argument against the 'nostalgic' practices of the Federal Republic.